An intermittently moving bed adsorption process for carbon dioxide capture. (June 2016) - Son, Yongho; Won, Wangyun; Lee, Taesoo; Lee, Kwang Soon
Highlights: A novel intermittently-moving-bed adsorption (I-MBA) process for CO2 capture. A process model and relevant operation strategy for the I-MBA process. Performance was analyzed through experiments and numerical simulation. Abstract: The goal of this study is to propose an intermittently-moving-bed adsorption (I-MBA) process as a potentially viable technology for CO2 capture from large CO2 sources. In the I-MBA process, sorbent particles are circulated between adsorption and desorption beds intermittently by the operation of on–off valves. The associated process model and the relevant operational strategy for the I-MBA process were also proposed. The intermittent migration of the adsorbent mass was described by the model as an intermittent reset and a transition of bed state variables. A heat transfer enhancement factor was devised to express the effect of the local mixing of adsorbent particles, and the relevant parameter values were identified using experimental data. To ensure numerically stable calculations, especially when the two disjoint profiles are concatenated by adsorbent moving, a method that adaptively adjusts the number and location of collocation points was also developed. The performance of the I-MBA process was thoroughly analyzed through experiments and numerical simulations for various cases of the operation sequence. The proposed process was evaluated to produce CO2 with a purity of over 95% and a recover of over 83%.